Translocação de fungicida sistêmico em feijoeiro (Phaseolus vulgaris L) inoculado com Uromyces phaseoli typica Arth - Rodrigues Almeida , Álvaro Manuel; Martins Chaves , Geraldo; Zambolim , Laércio; Maffia de Oliveira, Laede (Revista Ceres, 2025)
Upward, downward and lateral translocation of the systemic fungicide oxicarboxin in primary and trifoliate bean leaves was studied. Fifteen-day-old bean (Phaseolus vulgaris L. cv. ‘Pinto 111’) leaves inoculated with the rust Uromyces phaseoli typica Arth. were used. OXicarboxin was applied at the concentration of 2.000 ppm by spraying or by immersing the leaf in a suspension of the fungicide, with or without a coadjuvant, for periods of one half, one, three, six, and twelve hours. Two coadjuvants were tested, Esapon and Extravon.